Differentiated instruction in ESL Classrooms: insights from ESL Primary School Teachers - Nurul Hidayah Umar; Azlina Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2024)
In today’s classroom, teaching diversified skills with a conventional one-size-fits-all approach is unsuitable for the student’s development. Students with mixed abilities are unable to learn effectively when teachers implement lessons that treat the class as homogenous. This study therefore aims at examining teachers’ perceptions towards the management of differentiated instruction in mixed-ability ESL classes for primary school pupils. It is to seek the in-depth teachers’ perception of the familiarity of differentiated instructions, the types of differentiated instruction they used, the challenges they faced. To integrate two data sets and gain more information, the study was carried out with a case study design based on mixed methods. The participants were selected using a purposive sampling procedure involving 30 teachers at 17 Primary Schools in the Labuan Federal Territory. Data were collected employing questionnaires, and Open-ended Interviews; the results were analyzed descriptively with frequency, percentage, mean value, and standard deviation. The findings of this research study revealed that teachers’ perceptions have a positive impact on the use of differentiated instruction in ESL classrooms. However, the challenges they faced became barriers for them to implement the Differentiated Instruction in the classrooms. In conclusion, further discussions were held on some research implications and recommendations. This will provide additional value to existing research, contributing to the opening of an opportunity for teachers to enhance their knowledge and consistently use differentiated teaching.